KEPEMIMPINAN PELAYAN (SERVANT LEADERSHIP) SEBAGAI GAYA KEPEMIMPINAN UNTUK KEMAJUAN ORGANISASI - Astohar, Astohar (STIE Totalwin Semarang, 2012)
A company will succeed or fail even largely determined by the leadership. Leaders establish direction by developing a vision for the future, then communicate to everyone and inspire these people in the face of all odds. Servant leadership simultaneously can improve employees personal growth and improve the quality and service institutions begun all personal involvement of every member of the organization in the decision-making process as well as ethical behavior and responsible. Style is a servant leader model that optimizes the empowerment and development of members of the organization by making his followers as whole human beings with the essence is to serve others. Aspects of ministry leaders are serving the heart, the head of the serving, serving hand . The focus of the servant leader is employee development, the creation of added value for customers, creating customer satisfaction and continuous success. The dimensions of servant leaders are : Altruistic calling, Emotional Healing, Wisdom, Persuasive mapping, Organizational stewardship, Humility, Vision and Service Â Keyword : Servant leadership, organizational